Performance of mesophilic biohydrogen-producing cultures at thermophilic conditions. (September 2015) - Gupta, Medhavi; Gomez-Flores, Maritza; Nasr, Noha; Elbeshbishy, Elsayed; Hafez, Hisham; Hesham El Naggar, M.; Nakhla, George
Highlights: Effect of temperature shock to mesophilic anaerobic digester sludge was assessed. Co-fermentation of starch, and cellulose was assessed. Mesophilic co-fermentation of starch and cellulose increased the H2 yield by 26%. Thermophilic co-fermentation did not show any enhancement in H2 yield. Higher overall rates at mesophilic conditions than thermophilic conditions. Abstract: In this study, batch tests were conducted to investigate the performance of mesophilic anaerobic digester sludge (ADS) at thermophilic conditions and estimate kinetic parameters for co-substrate fermentation. Starch and cellulose were used as mono-substrate and in combination as co-substrates (1:1 mass ratio) to conduct a comparative assessment between mesophilic (37 °C) and thermophilic (60 °C) biohydrogen production. Unacclimatized mesophilic ADS responded well to the temperature change. The highest hydrogen yield of 1.13 mol H2 /mol hexose was observed in starch-only batches at thermophilic conditions. The thermophilic cellulose-only yield (0.42 mol H2 /mol hexose) was three times the mesophilic yield (0.13 mol H2 /mol hexose). Interestingly, co-fermentation of starch–cellulose at mesophilic conditions enhanced the hydrogen yield by 26% with respect to estimated mono-substrate yields, while under thermophilic conditions no enhancement in the overall yield was observed. Interestingly, the estimated overall Monod kinetic parameters showed higher rates at mesophilic than thermophilic conditions.